The power of feedback in an online learning environment - Pramela Krish, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
This paper takes a closer look at human interaction between the instructors and learners and among learners during learning in an online environment. An attempt was made to explore and analyse the power of feedback during online tutorials for English courses in a synchronous mode of learning. Based on learner responses to statements via a questionnaire and interviews, the paper shares the reflection of learners to oral and written feedback received during their online tutorials and how the feedback helped in improving their language literacy. Data from transcripts of online lessons will also be used to illustrate what is meant by feedback during online tutorials.The main findings of the study suggest that feedback has a positive impact on the online learners. The feedback of the instructors was much valued. Like the face-to-face mode of teaching and learning, it is clear that feedback on the electronic mode can help to enhance the language learning literacy.